THE FACTORS OF SATISFACTION ON E-LEARNING USAGE AMONG UNIVERSITI MALAYSIA KELANTAN STUDENTS - Nursuhaila Zaili; Leow Yep Moi; Noor Asmiera Yusof; Mohammad Nurhaaza Hanfi; Mohd Hafizie Suhaimi (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2019)
With the development of information and communication technology, E-Learning has been become one of the modern educations in a student’s life in term of academic. Elearning is a computer-based learning environment that allows learners and teachers to interact virtually through an open system. This research attempts to examine the factors that influence the student E-Learning satisfaction in Universiti Malaysia Kelantan. Independent variables included in this study are student factor, instructor factor, design factor, course factor, technical factor and student e-learning satisfaction as dependent variable. Literature reviews were provided to better understanding on this proposed conceptual framework. An aggregate of 368 responses of students in Universiti Malaysia Kelantan is collected in this survey. The research adopts a quantitative approach to examine critical factors that influence e-learning satisfaction. The data collected by survey questionnaire and data analysed by Statistical Package for Social Science (SPSS)